2024
DOI: 10.1126/science.adl2931
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh energy storage in high-entropy ceramic capacitors with polymorphic relaxor phase

Min Zhang,
Shun Lan,
Bing B. Yang
et al.

Abstract: Ultrahigh–power-density multilayer ceramic capacitors (MLCCs) are critical components in electrical and electronic systems. However, the realization of a high energy density combined with a high efficiency is a major challenge for practical applications. We propose a high-entropy design in barium titanate (BaTiO 3 )–based lead-free MLCCs with polymorphic relaxor phase. This strategy effectively minimizes hysteresis loss by lowering the domain-switching barriers and enhances the breakdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Zhang et al explored the domain structures of BaTiO 3 -based high-entropy ceramics using TEM and found that the domain size decreased to 0.8–3.6 nm with increasing entropy. The nanodomains were accompanied by improved relaxation features, which were closely relevant to local composition disorder in high-entropy systems . According to these reports, it can be believed that in the present work, the local random field induced by increasing entropy can destroy the long-range ordered ferroelectric domains, which makes the large-scale domains evolve into small-scale domains, resulting in strong relaxation behavior.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Zhang et al explored the domain structures of BaTiO 3 -based high-entropy ceramics using TEM and found that the domain size decreased to 0.8–3.6 nm with increasing entropy. The nanodomains were accompanied by improved relaxation features, which were closely relevant to local composition disorder in high-entropy systems . According to these reports, it can be believed that in the present work, the local random field induced by increasing entropy can destroy the long-range ordered ferroelectric domains, which makes the large-scale domains evolve into small-scale domains, resulting in strong relaxation behavior.…”
Section: Resultssupporting
confidence: 50%
“…The nanodomains were accompanied by improved relaxation features, which were closely relevant to local composition disorder in high-entropy systems. 36 According to these reports, it can be believed that in the present work, the local random field induced by increasing entropy can destroy the long-range ordered ferroelectric domains, which makes the large-scale domains evolve into small-scale domains, resulting in strong relaxation behavior. Furthermore, Figure 4h shows that the tan δ values of the asprepared samples are small and decrease with the increasing BNCBSTN content, indicating that BNCBSTN addition can reduce the dielectric loss.…”
mentioning
confidence: 65%
“…Recently, researchers have made considerable investments in lead-free relaxor ferroelectric/antiferroelectric ceramics, which include NaNbO 3 (NN), 3,4 K 0.5 Na 0.5 NbO 3 (KNN), 5,6 BaTiO 3 (BT), 7,8 Bi 0.5 Na 0.5 TiO 3 (BNT), 9–11 and BiFeO 3 (BF) 12,13 ceramics. With a 3.4 eV broad band gap and significant polarization responses, NN-based ceramics are regarded as one of the potential choices among them.…”
Section: Introductionmentioning
confidence: 99%